Engineering of indole-based tethered biheterocyclic alkaloid meridianin into β-carboline-derived tetracyclic polyheterocycles via amino functionalization/6-endo cationic π-cyclization - Agarwal, Piyush Kumar; Dathi, Meena Devi; Saifuddin, Mohammad; Kundu, Bijoy (Beilstein Journal of Organic Chemistry, 2012)
A mild, efficient and versatile method has been developed for the construction of a functionalized natural product, meridianin, and its post conversion to pyrimido-β-carboline by cationic π- cyclization. The strategy involves the introduction of an amino group at the C-5 of the pyrimidine ring and utilizing the nucleophilictiy of the C-2 in the indole ring to facilitate cationic π-cyclization.
Keywords: cyclization; indole; meridianin; natural products; nitrogen heterocycles